Computer-assisted navigation in oral and maxillofacial surgery: A systematic review - Nourah M Alkhayatt; Hadeel H Alzahrani; Suhael Ahmed; Bassam M Alotaibi; Rayan M Alsaggaf; Abdulelah M ALAlmuaysh; Abdulrahman A Alomair (Elsevier, 2024)
Background: The term "navigation" describes a device that can pinpoint critical anatomical features, the most direct path to the target, and the optimal surgical orientation. This study aimed to conduct a comprehensive literature search on computer-assisted navigation for use in oral and maxillofacial surgery. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, relevant studies were retrieved from five electronic databases: Medline, Web of Science, PubMed, Google Scholar, and Saudi Digital Library (SDL). The central question was, "Does the computer-assisted navigation system improve the outcome of surgical procedures in the oral and maxillofacial region?" The Cochrane Risk of Bias 2 was used to determine the various types of bias. Results: Post-traumatic midfacial reconstruction is one of the many fields that have benefited from the use of computer-assisted navigation because of its reliability. It can also be used to extricate difficult foreign entities from the operative zone. Locating critical anatomical components, communicating the surgical plan to the patient, and verifying surgical success can improve the function and appearance of patients with dentofacial abnormalities. In addition, it decreases the surgical error margin and duration. Conclusion: Computer-assisted navigation is promising in surgical practice. The accuracy of surgery can be significantly enhanced by first planning the process in a virtual environment and then performing it under close supervision in real time. In addition, the time required for preoperative planning and surgery can be reduced by creating and improving software programs.